Jobs, Recovery, and Peacebuilding in Urban South Sudan - von der Goltz, Jan (World Bank, Washington, DC, 2021)
After years of conflict, there is an opportunity for peace in South Sudan, but an effective economic recovery process must underpin the political settlement. The aim of this work is to inform policy for more productive urban jobs in peacebuilding and recovery in South Sudan and for first steps toward private sector development. To this end, this report studies the main urban centers of South Sudan, with a focus on those that are part of the partnership for recovery and resilience (PfRR). The goal of this report is to inform policy for the first few steps toward peacebuilding and recovery. Findings in this report are based on data analysis on urban jobs, including the self-employed and household activities that are the norm for most workers. This synthesis report summarizes findings from four technical studies on: (i) urban job activities and welfare outcomes, (ii) the macro-economic framework, (iii) markets and market-based agriculture, and (iv) businesses and non-profit organizations. This synthesis report proceeds as follows: part one, introductory section explains objectives and methodology of the research and gives some country context. Part two discusses empirical findings on: (i) challenges of supporting jobs and livelihoods; (ii) the macro-fiscal environment for jobs; (iii) markets and market-linked agriculture; (iv) jobs in businesses and non-profit organizations, and (v) constraints limiting economic activity. A discussion of policy and operational implications including some costing of recovery concludes the report.